PO43 Modulation of Oxidative Stress by Uchuva and Mamey Extracts: Evaluation using DCFH-DA at In Vitro and In Vivo Levels - Mercado Polo, Gisell Carolina; Conde Espinosa, Juan José; Franco , Luis Alberto; Castro Guerrero, Jenny Paola; Pájaro Bolívar, Indira Beatriz; Arroyo Gamero, Leonar Antonio; Palacio Taborda, Yuri Paola; Martelo Ramirez, Geraldine Maria; Caro Fuentes, Daneiva del Carmen (Revista Productos Naturales, 2025)
Oxidative stress results from an imbalance between reactive oxygen species (ROS) production and cellular antioxidant capacity, leading to biomolecular damage and various diseases. This study evaluated the modulatory effect of Physalis peruviana (golden berry) and Mammea americana (mamey) extracts on oxidative stress in in vitro and in vivo models using DCFH-DA. A significant reduction in ROS levels was observed in RAW 264.7 macrophages and mice with DSS-induced colitis, especially at high doses. These findings support their potential use in nutritional strategies to mitigate oxidative stress.
Keywords: Oxidative stress; reactive oxygen species; cape gooseberry; mamey; DCFH-DA